PENGEMBANGAN DESAIN SEPEDA ANAK USIA 7-12 TAHUN MENGGUNAKAN METODE RAPID ETHNOGRAPHY DAN SCAMPER - Marcellino Aditya Mahendra; Rini Dharmastiti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2020)
Title: Design Development of Bike for Kids (7-12 y.o) using Rapid Ethnography and SCAMPER Method Children by nature growth relatively fast. Their body expand in a short time that demand many things that they wear or use to meet their body accordingly. This to include also the need for their bicycle. In order to fulfill the needs of children’s comfort in cycling, some bicycles which are suitable with anthropometry of children’s body are required. With the existence of bicycle’s design which has longer durability than children’s bicycles in general, hence the children’s bicycle which will be designed would have sustainable design concept. Clark et al. (2009) states that sustainable design is a design concept which integrates 3 kinds of elements (people, profit, planet) and not merely an environmental-friendly concept. Developing a product with sustainable concept is not only done with a manipulation on materials which are bio-degradable, but also could be done with extending the lifespan of the product. Respondents which are targeted on this planning are children aged from 7 until 12 with their parents, since the children on this age range experience rapid growth. Not only the interests of the children aged from 7-12 as primer users which are concerned, but also their parents as secondary users. This matter is resulted from how the parents also play a role in choosing and buying the bicycle which will be used by their children.